1987
DOI: 10.1093/carcin/8.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-induced hepatocarcinogenesis: levels of activating and detoxifying enzymes in hepatocellular carcinomas induced by ciprofibrate

Abstract: It is generally held that altered areas, neoplastic nodules and hepatocellular carcinomas (HCC) induced by mutagenic chemical carcinogens are resistant to the effects of hepatotoxins. This characteristic is attributed to the marked decrease in activating (phase I) enzymes and a several-fold increase in detoxifying (phase II) enzymes. In previous studies, we have shown that hepatic neoplastic lesions induced by non-mutagenic peroxisome proliferators differed from mutagenic carcinogen-induced lesions by lacking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previous work has shown that gene expression patterns of mouse HCCs generated by the genotoxic carcinogen DENA are quite similar to human HCCs with the poorer survival, 45 whereas those of HCCs from mice treated with the nongenotoxic ciprofibrate, a potent peroxisome proliferator and a peroxisome proliferator-activated receptor a ligand, 46 were not. To explore whether a similar difference in the pattern of gene expression could take place in HCCs induced by genotoxic versus nongenotoxic conditions, hierarchical clustering analysis of gene expression patterns was applied to assess the relative similarities between HCCs generated by DENA þ TCP and those induced by TCP alone.…”
Section: Transcriptomic Analysis Reveals Hccs Cluster In Two Subclassesmentioning
confidence: 98%
“…Previous work has shown that gene expression patterns of mouse HCCs generated by the genotoxic carcinogen DENA are quite similar to human HCCs with the poorer survival, 45 whereas those of HCCs from mice treated with the nongenotoxic ciprofibrate, a potent peroxisome proliferator and a peroxisome proliferator-activated receptor a ligand, 46 were not. To explore whether a similar difference in the pattern of gene expression could take place in HCCs induced by genotoxic versus nongenotoxic conditions, hierarchical clustering analysis of gene expression patterns was applied to assess the relative similarities between HCCs generated by DENA þ TCP and those induced by TCP alone.…”
Section: Transcriptomic Analysis Reveals Hccs Cluster In Two Subclassesmentioning
confidence: 98%
“…longed administration, enzyme-altered foci appear (70) that are different from those induced by genotoxic chemicals that they do not contain increased carcino-gen-detoxifying enzymes (71,72). Later, AFP-negative cancers are seen (69).…”
Section: Ementioning
confidence: 99%
“…Comprehensive mechanistic studies indicate that the induction of phase II enzymes mediate not only cell detoxi cation and survival, but also cancer prevention (Bolton et al 1993;Kensler 1997;Kwak et al 2001). Moreover, it has been shown that alterations in phase II enzyme expression are associated with malignancy and cell transformation processes (Kitahara et al 1984;Rao et al 1987;Ramos-Gomez et al 2001, 2003Frohlich et al 2008).…”
Section: Introductionmentioning
confidence: 99%